Strategi KPU Solok Selatan untuk meningkatkan partisipasi memilih pada Pemilihan Bupati dan Wakil Bupati tahun 2020 - Ilham Saputra; Suryanef Suryanef; Al Rafni; Irwan Irwan (Journal of Civic Education, 2022)
This study aims to find out how the strategy is carried out by the South Solok KPU to increase voter participation in the 2020 Regent and Deputy Regent elections. The election of the Head of Blood is the embodiment of Democracy at the regional level. The direct election of regional heads entered into the electoral regime after the 2004 elections with the enactment of Law No. 32 of 2004 on regional government, which stipulates that a regional head is directly elected by the people. Furthermore, participation in electing the community is the main factor in the success of the Regional Head Election. This participation is not only limited to quantity but also based on quality. For this reason, efforts to increase voter participation in terms of quantity and quality are important. This type of research is qualitative research using descriptive methods and data collection techniques are in-depth interviews with research informants and study documentation. The informants of this study were the commissioners of the South Solok KPU and the KPPS officers for the 2020 Regional Head Elections. The location of this research was the South Solok KPU Office. The results obtained from this study are that the South Solok KPU strategy to increase voter participation in the 2020 Regent and Deputy Regent Elections is to conduct voter socialization and education to the public online, face to face and using mobile cars. Face-to-face socialization was carried out to 10 voter bases attended by a limited number of participants, and empowered Election Organizers to conduct socialization at their domicile. Online socialization is carried out using social media and other online applications, while socialization with mobile cars is carried out using a microphone installed in the car by inviting the public to exercise their right to vote on polling day. Keywords: Pilkada, Democracy, Participation